Research progress of vasculopathy in portal hypertension - Li, Tao (World J Gastroenterol, 2005)
Portal hypertension, one of the vascular diseases, not only has lesions in liver, but also changes in vascular structures and functions of extrahepatic portal system, systemic system and pulmonary circulation. The pathological changes of vasculopathy in portal hypertension include remodeling of arterialized visceral veins, intimal injury of visceral veins and destruction of contractile structure in visceral arterial wall. The mechanisms of vasculopathy in portal hypertension may be attributed to the changes of hemodynamics in portal system, immune response, gene modulation, vasoactive substances, and intrahepatic blood flow resistance. Portal hypertension can cause visceral hyperdynamic circulation, and the development and progression of visceral vasculopathy, while visceral vasculopathy can promote the development and progression of portal hypertension and visceral hyperdynamic circulation in turn. The aforementioned three factors interact in the pathogenesis of hepatic cirrhosis-induced portal hypertension and are involved in hemorrhage due to varicose vein rupture.